Els complements predicatius introduïts per una preposició en català antic. - RAMOS, JOAN-RAFAEL (Scripta)
This paper studies a phenomenon that has not been widely discussed in Catalan diachronic linguistics: non-verbal predications preceded by a preposition in Old Catalan. The analysis focuses essentially on two types of non-verbal predications: subject-related predicative complements and object-related predicative complements. Taking as study material the Corpus Informatizat del Català Antic (CICA), which covers texts from the 13th to the 17th centuries, a description is made of the prepositions capable of creating predicative complements (per, en, de, a, com and com a), although more specific emphasis is placed on the uses of the prepositions com and com a. In this respect, in view of the formal alternatives observed (com/com a) and the interest that it has aroused in the current normative language, a more detailed quantitative analysis is carried out, which shows the trends of use from both a geographical and diachronic point of view.